Behavioral Configuration of Mindfulness in Adolescents Through Identification of Narcissism, Trait Mindfulness, and Aggressiveness - Triyuni Lestari; Dini Rahma Bintari (Eduvest - Journal of Universal Studies, 2025)
Everyone has the capacity to turn their observations, ideas, memories, and imagination into actions, especially during the adolescent stage. This is because each person will naturally show an action as a result of self-actualization, thus behavior may be difficult to be controlled. Every teenager has their own way of achieving self-actualization, and some of them may display narcissistic behavior, in an effort to gain respect and admiration from others. The aim of the research is to analyze the configuration of mindfulness actions in adolescents through the identification of narcissism, trait mindfulness, and aggressiveness. This article's research is based on a narrative literature review. Based on the analysis that has been carried out, the configuration of mindfulness actions in shows that by applying mindfulness, people with narcissistic tendencies have increased mental toughness, better performance at work or school, and a higher sense of self-esteem, which makes them appear to be more courageous and assertive. Although narcissistic behavior has certain benefits to some degrees, there will be no benefit if it continues. A person with the trait of mindfulness is able to be very aware and alert of their environment. People will pay close attention to everything that happens around them. Having the attributes of mindfulness can make someone happier, less anxious, and more resistant to depression. Mindfulness is one of the suggested alternatives that can reduce levels of aggression. Hence, mindfulness is a quality that is beneficial to one’s life and can be cultivated.